Analisis Rencana Keuangan dan Manajemen Keuangan Masjid Dalam Mensejahterakan Masyarakat - Dewi Sartika Nasution; Hendra Harmain; Nurwani Nurwani (Jurnal Ilmiah Ekonomi Islam, 2023)
The mosque is one of the centers of guidance and development of the Islamic community. It requires a solid financial plan and financial management due to the large amount of donations. A good financial plan and financial management will encourage the welfare of the local community. This study aims to analyze the extent of the mosque's financial plan and financial management, and how much it contributes to community welfare. The method used by researchers in this study is descriptive qualitative method. The data collection techniques used in this study were observing the environment of the three mosques and interviewing resource persons at the five mosques in Padang Lawas Regency. The results of this study are that the financial plan and financial management have been managed quite well. The contribution of the mosque's financial plan and financial management has also been quite large in generating community welfare. Through an independent business at the Miftahul Jannah Grand Mosque in the form of a drinking water depot, the community has felt its influence, namely the price for a gallon of drinking water sold cheaper than the market price. Empowerment of orphans and donations to the poor are also carried out by these five mosques.